Evaluation of geological formation for potential groundwater aquifer by integrated geophysical techniques - Yusof, Nor Farhani (2018)
Electrical resistivity method is the most popular method among geophysical techniques in groundwater exploration mainly in evaluating hydrogeological properties of the subsurface. However, electrical resistivity method can only identify the subsurface resistance specifically the subsurface structure, not the groundwater potential zone. Other than that, different hydrogeological formations have different groundwater yield potential. Thus, by using integrated geophysical technique can give a better interpretation. The main objective is to determine the potential groundwater zone in different types of soil and rock categories. A study on 2D geo-electrical was conducted at Taiping, Perak, Serdang and Jenderam Hilir, Selangor. The technique of geophysics analysis was carried out by using two geo-electrical method of electrical resistivity and induced polarization method for better interpretations in the same area. Field works have been carried out using Terrameter SAS 4000, Electric Selector ES1064 and LUND cable with electrode. Horizontal resistivity lines were proposed with length of 400m each by using Wenner-Schlumberger configuration. Electrical current was injected into the ground and two potential electrodes are measured resulting in voltage difference for electrical resistivity and transient decay for induced polarization. The images of 2D profile have been produced using Res2Dinv software through inversion method which provided detailed information of both the laterally and vertically geological structures based on their part. The Cluster Analysis of Hierarchical Agglomerative Clustering Analysis has been used to differentiate different types of soil and rock characteristic. The data from the electrical resistivity result in form of numerical value have been used in XLSTAT-Pro software by using Ward Method. The characteristic of alluvium can be classified to clay, silt, fine and medium sand, coarse sand, sand and gravel, and gravel. Otherwise, rock characteristics can be differentiated based on the stages of rock weathered. Induced polarization method resulted in the value of chargeability that has potential to determine the freshwater of the subsurface. Thus, the integration of geophysical technique and statistical analysis can identify the high potential of aquifer zone in different categories of formation. Through this study, it can save you time and cost, where groundwater potential can be determined without running the drilling process.